Proyecto de factibilidad para la creación de una empresa dedicada a la producción e industrialización de snacks, a base de miel como derivado de caña de azúcar, ubicado en el Cantón San Miguel, y su comercialización en la Provincia de Bolívar - Arias Lara, Carmen Julia (2013)
Sugarcane is a crop that allows a wide diversity of production, reason why you it’s possible to find on the market derived as: sugar, brown sugar, and alcohol, a situation that may well be attributed to the Province of Bolivar this activity is not managed correctly, as most producers do not follow proper planning, so that they can make efficient use of the great potentialities of the Province. The present study determines that the Province of Bolivar is an appropriate place for a project focused on the marketing of honey-based snacks such as sugar cane derivative thereof being selected the Canton San Miguel de Bolivar as the most appropriate for production and industrialization. In order to establish the company, you need to manage relevant theoretical aspects as market research, unmet demand, organizational culture, enterprise engineering, strategic planning, brand positioning and financial evaluation of the project.